Research on Methods of "Touching the World" ―The Aim of the Exhibit Area of Tactile Learning in Japan’s National Museum of Ethnology - Hirose, Kojiro (Disability Studies Quarterly, 2013)
The author acknowledges that blind and visually impaired people constitute only about one percent of annual visitors to his museum, but has nevertheless implemented tactile exhibits to enhance the learning and enjoyment of everyone. He describes tactile workshops he has developed to train visitors to get the most out of handling and exploring objects through touch. Key words: Japan’s National Museum of Ethnology, blind and visually impaired Japanese, tactile exhibits, universal design in museums.